2022
DOI: 10.1186/s12909-022-03224-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on Saudi medical students’ career choices and perceptions of health specialties: findings from a national cross-sectional study

Abstract: Background The COVID-19 pandemic has had a devastating effect on people across the globe. Its impact on medical students’ education has also been profound. Here, we aimed to comprehensively determine the nature of this impact on their choice of specialty. Method A cross-sectional study was conducted among medical students in Saudi Arabia during the pandemic from May to June 2021. Data collected from 1984 medical students were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Additionally, the pandemic prompted a reassessment of healthcare priorities on a global scale. Although studies have demonstrated this phenomenon in various regions [ 25 , 26 ], there remains a dearth of such research in the context of France.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the pandemic prompted a reassessment of healthcare priorities on a global scale. Although studies have demonstrated this phenomenon in various regions [ 25 , 26 ], there remains a dearth of such research in the context of France.…”
Section: Discussionmentioning
confidence: 99%